IDENTIFICATION AND SOLUTIONS IN DEVELOPMENT OF COMMUNITY-BASED AGROTOURISM: CASE STUDY IN THE TUTUR SUBDISTRICT OF PASURUAN DISTRICT - Syahfirin Abdullah, M. Syamsul Ma'arif Martani Husaini, Tajuddin Bantacut dan Ricky Avenzora (Jurnal Teknologi Industri Pertanian, 2012)
ABSTRACT Tourism is becoming advantage commodity, because it’s able to contribute significantly on foreign exchange from non oil and gas commodities.  Nowadays, Indonesia is 60th ranking and left behind from other Asian countries. This was  caused by some problems of Indonesian tourism. The objectives of this research were  to identify and structuralize some problems in agrotourism in Tutur Subdistrict and to obtain the solution for its development. This research was  case study using the systemic approach.  Data were  analyzed by Interpretative Structural Modelling (ISM).  The result of this research shows that Tutur Subddistrict agrotourism development have many problems.  Main problems were  low  quality of human resources management and  weakness of business orientation.  The solution would be to develop training on agrotourism and business to human resources in Tutur subdistrict , so that they can work  and  manage their business professionally. Keywords: agrotourism,  ISM, human resources quality, business , solution, professional